Entecavir vs Tenofovir in Hepatocellular Carcinoma Prevention in Chronic Hepatitis B Infection: A Systematic Review and Meta-Analysis. Issue 10 (6th October 2020) - Cheung, Ka Shing; Mak, Lung Yi; Liu, Sze Hang; Cheng, Ho Ming; Seto, Wai Kay; Yuen, Man Fung; Lai, Ching Lung
Abstract : INTRODUCTION: Entecavir (ETV) and tenofovir disoproxil fumarate (TDF) are recommended as first-line therapies for chronic hepatitis B (CHB) infection. Although both drugs reduce hepatocellular carcinoma (HCC) risk, their comparative effectiveness remains controversial. We aimed to determine whether TDF is superior to ETV in preventing HCC. METHODS: PubMed, Embase, and Cochrane Library from inception until June 9, 2020, were searched according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Key terms included entecavir, tenofovir, and hepatocellular carcinoma. The adjusted hazard ratios (HRs) were pooled using a random effects model. Heterogeneity among studies was assessed by the Cochran Q test and I 2 . RESULTS: Thirteen observational studies (4 of which were conference abstracts) were included with 85, 008 patients with CHB (ETV: 56, 346; TDF: 28, 662). TDF was associated with a lower HCC risk (adjusted HR [aHR]: 0.81; 95% confidence interval [CI]: 0.67–0.99). This beneficial effect was present in cirrhotic patients (aHR: 0.73; 95% CI: 0.62–0.85) and retrospective cohort studies using electronic data sets (aHR: 0.63; 95% CI: 0.51–0.78). However, this beneficial effect did not reach statistical significance for noncirrhotic patients (aHR: 0.83, 95% CI: 0.51–1.35) and retrospective/prospective cohort studies using clinical records (aHR: 0.97; 95% CI: 0.80–1.18). DISCUSSION: TDF was associated with a lower HCC risk compared with ETV among patients with CHB, particularly cirrhotic patients. Further prospective large-scale studies with longer follow-up periods were required to identify specific subgroups that will benefit most from TDF.